Multi readers detection in adaptive RFID middleware - Mohd. Hashim, Siti Zaiton (Institute of Electrical and Electronics Engineers, 2008)
Compared to traditional middleware, adaptive middleware enables modification of the behavior of distributed applications in response to some changes in functional requirements or operating conditions. RFID applications in particular have grown widely and are used in many purposes such as supply chain management and ubiquitous computing. Implementing adaptive characteristic in RFID middleware will increase the capability of adaptation to specific environment involving different reader/tag, different applications, and different platforms. Based on an extensive study conducted, standard features that reflect the functionalities of RFID middleware and adaptive features that represent the non-functionalities of RFID middleware have been identified. Multi-reader detection indicates one important feature in adaptive RFID middleware as it offers flexibility in deployment of various manufactured-readers. This paper discusses the successful implementation of multi-reader detection feature in the proposed adaptive RFID middleware.